PENGARUH PERSEPSI KEAMANAN, KEMUDAHAN BERTRANSAKSI, KEPERCAYAAN TERHADAP TOKO DAN PENGALAMAN BERBELANJA TERHADAP MINAT BELI SECARA ONLINE PADA SITUS JUAL BELI TOKOPEDIA.COM - Alwafi, Fachrizi; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the influence of security, ease of transaction, consumer confidence and the shopping experience to the online buying interest in tokopedia.com.Â This study uses a questionnaire distributed to a sample of 100 respondents were divided into two (2) groups based on residence between Semarang with outside Semarang, non probability sampling. The sampling technique is using purposive sampling, because the researchers used intentionally separate consideration in choosing members of the population are considered to be appropriate in providing the information needed for research.Based on the analysis that has been done, can present some research findings are: 1) the variable perception of safety (X1) the greatest positive effect on the variable interest purchase online at tokopedia.com; 2) perception of ease (X2) the third largest positive effect on the variable interest purchase online at tokopedia.com (Y); 3) the perception of trust (X3) the second largest positive effect on the variable interest purchase online at tokopedia.com (Y), and 4) the perception of the experience (X4) has no effect on the variable interest purchase online at tokopedia.com (Y) .